2018
DOI: 10.3389/fpsyg.2018.01829
|View full text |Cite
|
Sign up to set email alerts
|

Anthropomorphic Design: Emotional Perception for Deformable Object

Abstract: Despite the increasing number of studies on user experience (UX) and user interfaces (UI), few studies have examined emotional interaction between humans and deformable objects. In the current study, we investigated how the anthropomorphic design of a flexible display interacts with emotion. For 101 unique 3D images in which an object was bent at different axes, 281 participants were asked to report how strongly the object evoked five elemental emotions (e.g., happiness, disgust, anger, fear, and sadness) in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Prior work has shown that people will establish relationships with machines possessing human-like characteristics (de Visser et al 2016). Giving computer entities anthropomorphic elements is hence integral to successful design (Lee, Baek, and Ju 2018). Scholars have also argued that anthropomorphism cues can evoke human perceptions (Araujo 2018;Epley, Waytz, and Cacioppo 2007;Rietz, Benke, and Maedche 2019), which affect users' perceptions and behavioral intentions related to humanized entities (Puzakova, Kwak, and Rocereto 2013;Qiu and Benbasat 2009).…”
Section: Effects Of Anthropomorphic Cues On Consumers' Usage Intentionsmentioning
confidence: 99%
“…Prior work has shown that people will establish relationships with machines possessing human-like characteristics (de Visser et al 2016). Giving computer entities anthropomorphic elements is hence integral to successful design (Lee, Baek, and Ju 2018). Scholars have also argued that anthropomorphism cues can evoke human perceptions (Araujo 2018;Epley, Waytz, and Cacioppo 2007;Rietz, Benke, and Maedche 2019), which affect users' perceptions and behavioral intentions related to humanized entities (Puzakova, Kwak, and Rocereto 2013;Qiu and Benbasat 2009).…”
Section: Effects Of Anthropomorphic Cues On Consumers' Usage Intentionsmentioning
confidence: 99%
“…It can be used to describe physical or mental animal-human behavior interaction (e.g., dogs or cats mimic human behavior by showing teeth or smiling). Because humans have a tendency to be more emotionally comfortable with things that are similar to themselves, researchers in psychology field pointed out that anthropomorphism can influence human psychology and behavior (e.g., humans are intimate to dogs that can show human-like comforts) (Lee et al, 2018 ). With the development of artificial intelligence, technology is displaying anthropomorphism characteristics and interact with humans as well.…”
Section: Introductionmentioning
confidence: 99%
“…For deformable object perception, previous works learn and leverage appearance and geometric information [36,33,40], softness [3], visual-tactile sensation [7], shape completion [4], emotional perception [24], optimal perception [8] and the continuity of perception [29,9,22]. The manipulation is challenging for its high complexity.…”
Section: Perceive and Manipulate Deformable Objectsmentioning
confidence: 99%